Pengaruh Mekanisme Corporate Governance Terhadap Nilai Perusahaan Pada Perusahaan Consumer Goods - Kartika Aprilia Benhardy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to examine the effect of corporate governance mechanisms on firm value. Proxy of corporate governance variables is managerial ownership, institutional ownership, board of directors, independent board of commissioner and audit committee. The research sample is consumer goods company listed on BEI in 2012-2016. The sampling technique used is purposive sampling to get 27 companies from 40 consumer goods companies listed on BEI with total of observation is 135 observation data during 5 years. Data analysis techniques using multiple regression analysis panel data by Eviews 9 software. Firm value is measured using Tobin’s Q. In addition, hypothesis testing was performed using t-statistic with significance level of 5%. Company value is measured using Tobin's Q. Based on the results of the analysis, it is found that managerial and independent board ownership variables have a negative and significant influence on firm value. Institutional ownership variables have a positive and significant influence on firm value. While the other two variables, the board of directors and audit committee has no significant effect on firm value.